Antibiotic resistance: An ethical challenge - Littmann, Jasper; Buyx, Alena; Cars, Otto (International Journal of Antimicrobial Agents, 2015)
In this paper, we argue that antibiotic resistance (ABR) raises a number of ethical problems that have not yet been sufficiently addressed. We outline four areas in which ethical issues that arise in relation to ABR are particularly pressing. First, the emergence of multidrug-resistant and extensively drug-resistant infections exacerbates traditional ethical challenges of infectious disease control, such as the restriction of individual liberty for the protection of the public's health. Second, ABR raises issues of global distributive justice, both with regard to the overuse and lack of access to antibiotics. Third, the use of antibiotics in veterinary medicine raises serious concerns for animal welfare and sustainable farming practices. Finally, the diminishing effectiveness of antibiotics leads to questions about intergenerational justice and our responsibility for the wellbeing of future generations. We suggest that current policy discussions should take ethical conflicts into account and engage openly with the challenges that we outline in this paper.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Antibiotic resistance; Distributive justice; Ethics; Health policy